Analisis Perbandingan Metode Simple Multi Attribute Rating Technique (SMART) Dan Metode Preference Selection Index (PSI) Dalam Penentuan Guru Terbaik SD N 14 Seluma - Docky Agresma; Dimas Aulia Trianggana; Desi Mahdalena (UNIVED Press, 2026)
Objective teacher performance assessment is an important step in improving the quality of education in schools. This study aims to analyze the comparison between the SMART (Simple Multi Attribute Rating Technique) method and the PSI (Preference Selection Index) method in determining the best teachers at SD Negeri 14 Seluma based on teacher performance assessment data for the 2023/2024 academic year. The comparison was conducted through three main aspects, namely processing time, final assessment results, and accuracy levels measured using a confusion matrix. The results showed that the SMART method had a faster processing time than the PSI method. However, both methods produced the same final results in determining the best teachers, with identical rankings. In terms of accuracy, both the SMART and PSI methods showed the same accuracy level of 80%. System testing using the blackbox method also showed that the developed application functions well and is capable of providing accurate recommendations for the best teachers each year.